Perancangan Sistem Informasi Aplikasi Absensi Berbasis Website di Madrasah Aliyah Sabilul Hasanah - Aqil, Ibnu; Hadinata, Novri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
Abstract The use of information technology in the world of education is now a necessity to improve efficiency and effectiveness in the learning process and school administration. Madrasah Aliyah Sabilul Hasanah in Banyuasin as a developing secondary education institution is also not free from the need to utilize information technology to improve the quality of administrative management, especially in terms of recording student attendance. Attendance is one of the important aspects in school administration management that affects the smoothness of the learning process. The existence of an integrated attendance information system can help facilitate the process of recording and monitoring student attendance and minimize administrative errors that may occur. By being website-based, this information system can be easily accessed by various related parties, such as teachers, administrative staff, and parents of students.